The Implementation of Problem-Based Learning to Increase Students’ Conceptual Understanding According to a Christian Perspective - Hans David Lasut; Jacob Stevy Seleky (Universitas Pelita Harapan, 2016)
In the world of education, it is important that the teacher considers knowledge that students gain in school that can be applied in various situations in a student’s life either during the course of their formal education or when facing real-life problems. The inability to apply knowledge is termed as a lack of conceptual understanding. The researcher hypothesized that Problem Based Learning (PBL) will overcome this problem. The aim of this research is to determine whether the implementation of PBL can increase student’s conceptual understanding and to discover effective ways to implement PBL in order to increase the student’s conceptual understanding. This research is Classroom Action Research and is two-cycle research where the researcher used written tests, questionnaires, interviews of teachers and students, teacher’s observation forms, and journal reflections as instruments to measure the student’s conceptual understanding and the implementation of PBL based on a Christian perspective. Based on the analysis and discussion, it can be concluded that the implementation of problem-based learning can increase the student’s conceptual understanding according to a Christian perspective.BAHASA INDONESIA ABSTRAK: Dalam dunia pendidikan, sangatlah penting bagi seorang guru untuk memperhatikan bahwa pengetahuan yang sudah siswa pelajari di sekolah dapat diaplikasikan dalam berbagai situasi baik saat siswa di sekolah maupun ketika mereka diperhadapkan dengan masalah dalam kehidupan. Ketidakmampuan siswa untuk mengaplikasikan pengetahuan yang sudah didapatkan dapat disebut sebagai kurangnya penguasaan konsep. Peneliti memutuskan untuk menggunakan Metoda Pembelajaran Berbasis Masalah (MPBM) untuk mengatasi masalah ini. Tujuan dari penelitian ini adalah untuk menemukan apakah penerapan MPBM dapat meningkatkan penguasaan konsep siswa dan langkah-langkah efektif untuk menerapkan MPBM dengan maksud untuk meningkatkan penguasaan konsep siswa. Metode penelitian yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang berlangsung selama dua siklus di mana peneliti menggunakan ujian tertulis, angket siswa, wawancara siswa, wawancara guru, lembar observasi guru, dan jurnal refleksi sebagai instrumen untuk mengukur penguasaan konsep siswa dan penerapan MPBM. Berdasarkan hasil analisis dan diskusi, maka dapat disimpulkan bahwa penerapan MPBM dapat meningkatkan penguasaan konsep siswa dalam mempelajari peluang secara perspektif Kristen.